Wage and mobility effects of trade and migration on the Austrian labour market - Helmut Hofer; Peter Huber (Institute for Advanced Studies (IHS), 2001)
This study analyses the effect of trade and migration on wages and labour market mobility. We estimate wage growth equations and a multinomial logit mobility equation on an individual data set for 1991 to 1994. We find substantial differences in the reactions of white and blue-collar workers wages and mobility to trade and migration. In Austria exports have a positive and imports a negative impact on wage growth only for blue-collar workers. Migrants also reduce only blue-collar workers wage growth. Our results indicate that higher imports and an inflow of migrants reduce sectoral mobility of all types of workers. The risk of being out of work by contrast is increased by migration and imports for only blue-collar workers, but reduced by exports for all types of workers. In general, our results suggest enlargement of the EU would have only small effects on the Austrian labour market.
Keywords: F16; F31; F15; 330; wages; migration; trade; Lohn; Arbeitsmobilität; Internationale Arbeitsmobilität; Außenwirtschaft; Österreich